Effects of histidine supplementation on amino acid metabolism in rats - Holeček, M; Vodeničarovová, M (Physiological research, 2020)
Histidine (HIS) is investigated for therapy of various disorders and as a nutritional supplement to enhance muscle performance. We examined effects of HIS on amino acid and protein metabolism. Rats consumed HIS in a drinking water at a dose of 0.5 g/l (low HIS), 2 g/l (high HIS) or 0 g/l (control) for 4 weeks. At the end of the study, the animals were euthanized and blood plasma, liver, soleus (SOL), tibialis (TIB), and extensor digitorum longus (EDL) muscles analysed. HIS supplementation increased food intake, body weight and weights and protein contents of the liver and kidneys, but not muscles. In blood plasma there were increases in glucose, urea, and several amino acids, particularly alanine, proline, aspartate, and glutamate and in high HIS group, ammonia was increased. The main findings in the liver were decreased concentrations of methionine, aspartate, and glycine and increased alanine. In muscles of HIS-consuming animals increased alanine and glutamine. In high HIS group (in SOL and TIB) increased chymotrypsin-like activity of proteasome (indicates increased proteolysis); in SOL decreased anserine (beta-alanyl-N1-methylhistidine). We conclude that HIS supplementation increases ammonia production, alanine and glutamine synthesis in muscles, affects turnover of proteins and HIS-containing peptides, and increases requirements for glycine and methionine.
Keywords: histidin; Amino Acids; náhodné rozdělení; Dietary Supplements; zvířata; Histidine; mužské pohlaví; Proteasome Endopeptidase Complex; potravní doplňky; svaly; Random Allocation; proteasomový endopeptidasový komplex; Rats, Wistar; potkani Wistar; Liver; Muscles; Animals; játra; Male; aminokyseliny